2021
DOI: 10.1155/2021/6466645
|View full text |Cite|
|
Sign up to set email alerts
|

Characterization of Lactic Bacteria Isolated from Raw Milk and Their Antibacterial Activity against Bacteria as the Cause of Clinical Bovine Mastitis

Abstract: The objectives of this study were the selection of lactic acid bacteria (LAB) isolated from raw milk and studying their technological properties and antibacterial activities against bacteria as the cause of cattle mastitis. Biochemical and molecular identification using 16S–23S rRNA gene spacer analysis and 16S rRNA gene sequencing highlighted the presence of three species: Lactiplantibacillus plantarum, Lactococcus lactis, and Levilactobacillus brevis. The enzymatic characterization followed by the determinat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…Different factors, including host, environment, seasons, and specific agent parasites, such as Staphylococcus Aureus (S. aureus) and Escherichia Coli (E. coli) are responsible for it. 20,21 Metal−organic frameworks (MOFs) and covalent organic frameworks have been considered as two types of organic materials, in the last few decades, which can be easily made and designed due to their properties. 22 In recent years, researchers have found great interest in semiconductor nanomaterials because of their remarkable physical and chemical properties, high surface area, and less toxicity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Different factors, including host, environment, seasons, and specific agent parasites, such as Staphylococcus Aureus (S. aureus) and Escherichia Coli (E. coli) are responsible for it. 20,21 Metal−organic frameworks (MOFs) and covalent organic frameworks have been considered as two types of organic materials, in the last few decades, which can be easily made and designed due to their properties. 22 In recent years, researchers have found great interest in semiconductor nanomaterials because of their remarkable physical and chemical properties, high surface area, and less toxicity.…”
Section: Introductionmentioning
confidence: 99%
“…Different factors, including host, environment, seasons, and specific agent parasites, such as Staphylococcus Aureus ( S. aureus ) and Escherichia Coli ( E. coli ) are responsible for it. 20 , 21 …”
Section: Introductionmentioning
confidence: 99%
“…In addition, such changes in metabolic pathways brought in more energy to produce much more secondary metabolite (including bacteriocin) during aerobic respiratory metabolism than fermentation. Besides bacteriocins, acetic acid, acetoin and diacetyl have been part and parcel of antimicrobial compounds [ 46 , 47 ].…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the positive effects of monensin and nisin on gastrointestinal tract pathogens may improve milk production (Alharbi & Alsaloom, 2021;Soltani et al, 2021). Reports (Mammi et al, 2021) stated contrasting results, with no effect of monensin supplementation on milk yield, fat, and protein content; however, McCarthy et al (2015) observed increased milk production in cows fed monensin.…”
Section: Milk Yield and Compositionmentioning
confidence: 99%